2021
DOI: 10.3349/ymj.2021.62.10.943
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Children with Autism Spectrum Disorder Using Data from a Large-Scale Korean National Cohort

Abstract: Purpose This study aimed to investigate the association between autism spectrum disorder (ASD) diagnosis and mortality among children using the data from a large-scale national cohort of Korean infants and children. We also explored the association between hearing impairment detected during early infancy and mortality. Materials and Methods We performed a retrospective cohort study using the nationwide claims data of the Republic of Korea. Children born between 2007 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We performed this retrospective study using information from the NHIS in Korea. We used data on ASD (codes F84.0, F84.1, F84.5, F88.8, or F88.9 according to the International Classification of Diseases [ICD], 10th revision), as in a previous study, through the homepage of the NHIS (http://www.nhis.or.kr) that provides various information [11]. This information is based on insurance claims submitted by doctors after examining ASD patients from 2011 to 2021.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…We performed this retrospective study using information from the NHIS in Korea. We used data on ASD (codes F84.0, F84.1, F84.5, F88.8, or F88.9 according to the International Classification of Diseases [ICD], 10th revision), as in a previous study, through the homepage of the NHIS (http://www.nhis.or.kr) that provides various information [11]. This information is based on insurance claims submitted by doctors after examining ASD patients from 2011 to 2021.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Previous studies may not have incorporated the income of the family into their research, [11][12][13][14]19,22 although some considered it a confounding factor. 23 A previous study showed that the mortality rate associated with ASD increased across all income classes. 20 Another study found no difference in the income of the family concerning ASD mortality.…”
Section: Introductionmentioning
confidence: 97%